TINGKAT KEPEDULIAN DAN SELF EFFICACY MAHASISWA UNIVERSITAS TERBUKA TERHADAP E-LEARNING - Padmo, Dewi; Julaeha, Siti (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2007)
Research on the level of apprehension and self efficacy of Universitas Terbuka’s students to E-learning was aimed at investigating the level of apprehension and self efficacy to e-learning as well as to prove the reasearch hypothesis that the apprehension stages has a significant corellation to the level of self efficacy in using e-leaning. The population of the study was Universitas Terbuka’s students registered to courses that offer online tutorials. The sample was choosen by a purposive random sampling technique from students from 4 faculties and magister program taken courses offered by online tutorial and registered by the most of the students. The result of the research gave a general picture of students’ self efficacy in using the Internet make use of e-learning in their study activities was considering in average category. The average score of students’ capability of using Internet was 3.73 from 6 Likert scale. The highest score of students’ capability in using the Internet was their ability in reading text. On the other hand, capability that considered low was students’s capability in creating a simple web page using teks, pictures, and links. The students’ awareness in using e-learning for their learning activities was varied. Based on 54.76% students who were using e-learing , 2.38% were in management stage, 21.43% at consequence stage, 9.52% in collaboration stage, and 21,43% in refocusing stage. The findings suggest a positive correlation between the students’ self-efficacy level in using Internet with their awareness in using e-learning.